2015
DOI: 10.1177/0886260515599656
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intoxicated Witnesses: Perception of Aggression and Guilt in Intimate Partner Violence

Abstract: Many witnesses to violent crimes are alcohol intoxicated, but research is lacking regarding how alcohol affects their perception of aggression and guilt. This study investigated to what extent alcohol intoxicated eyewitnesses differed from sober witnesses regarding how aggressive and guilty they perceived the involved parts in an intimate partner violence (IPV) situation. Eighty-seven healthy men ( n = 44) and women ( n = 43) were randomized to an alcohol group (0.7 g/kg) or a non-alcohol group. In a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Hence, a reduced amygdala activity due to intoxication seems to alter the perception of social stimuli, making social cues of “dangerousness” less anxiety provoking (see also Adolphs et al ., ; Deffenbacher, Bornstein, Penrod & McGorty, ), but also interpreting ambiguous social information as more hostile than sober persons do (Ogle & Miller, ). This is in line with a study on intoxicated witnesses to violence which found that intoxicated witnesses perceived the witnessed physical aggression as less severe, but the neutral interaction as more hostile, than sober witnesses did (Hildebrand Karlén, Roos af Hjelmsäter, Fahlke, Granhag & Soderpalm Gordh, ). The appraisal disruption model has also been cited in Hildebrand Karlén et al .…”
Section: Theories Proposed Relevant For When and Why Alcohol Impairs supporting
confidence: 87%
See 1 more Smart Citation
“…Hence, a reduced amygdala activity due to intoxication seems to alter the perception of social stimuli, making social cues of “dangerousness” less anxiety provoking (see also Adolphs et al ., ; Deffenbacher, Bornstein, Penrod & McGorty, ), but also interpreting ambiguous social information as more hostile than sober persons do (Ogle & Miller, ). This is in line with a study on intoxicated witnesses to violence which found that intoxicated witnesses perceived the witnessed physical aggression as less severe, but the neutral interaction as more hostile, than sober witnesses did (Hildebrand Karlén, Roos af Hjelmsäter, Fahlke, Granhag & Soderpalm Gordh, ). The appraisal disruption model has also been cited in Hildebrand Karlén et al .…”
Section: Theories Proposed Relevant For When and Why Alcohol Impairs supporting
confidence: 87%
“…This puzzle‐piece requires the perspective of the appraisal‐disruption model (Sayette, ), and entails that alcohol intoxication's pharmacological impact make anxiety‐invoking material less salient and risky situations perceived as less dangerous (see Pihl & Peterson, ; Sayette, ). Some of the basic results underlying the appraisal disruption model have been confirmed in a witness setting, and indicate that intoxicated witnesses (BAC = 0.04–0.10) perceive violence as less anxiety‐provoking compared to sober witnesses (Hildebrand Karlén et al ., ).…”
Section: Weighing Of the Theories: Usefulness In Light Of Research Onmentioning
confidence: 97%
“…Social judgements are important pieces of information that witnesses to interpersonal violence are asked to report, and research has shown that amygdala's function is impaired by anxiolytic agents such as alcohol and bensodiazepines (Buchanan et al, 2003;Curran, 2006). Even though laboratory studies seldom can recreate a life-like experience in witnessing violence, one laboratory study on intoxicated witnesses to violence has shown that these witnesses perceived the witnessed stimuli (a film) as less disturbing than sober witnesses (Hildebrand Karlén, Roos af Hjelmsäter, Fahlke, Granhag, & Söderpalm, 2015). The memory enhancing effect of moderate stress compared to neutral contexts over time found in previous research is thought to be partly due to a tendency to over time think about emotional information more often than neutral (Christianson, 1992), but also due to an influential role of the amygdala on memory formation (Adolphs et al, 2001).…”
Section: Combined Effects In Practice: Alcohol Emotional Activation mentioning
confidence: 99%
“…Previous results by Hildebrand Karlén et al () have suggested that intoxication at BAC level = 0.075 makes neutral interaction seems more aggressive, physical aggression seems more benign, and the IPV scenario seems less unpleasant. However, because the man in the present film was perceived as less attacking and the woman as more attacking by highly intoxicated participants compared with how the sober participants perceived them, this difference cannot solely be explained by an alcohol induced hostility bias.…”
Section: Discussionmentioning
confidence: 88%
“…Alcohol is also known to affect the consolidation of memories, primarily by decreasing neuronal activity within the hippocampus and medio‐temporal cerebral structures, thereby impairing the ability to associate incoming information to previously stored memories during the encoding process (Mintzer, ; Sayette, ; White, ; White, Matthews, & Best, ). Furthermore, alcohol disrupts the function of the amygdala, which both disrupts the process of memory consolidation and causes uncomfortable and anxiety‐inducing events to be perceived as generally less frightening and risk taking more likely (Buchanan, Karafin, & Adolphs, ; Hildebrand Karlén, Roos af Hjelmsäter, Fahlke, Granhag, & Söderpalm, ; Josephs & Steele, ; Sayette, ).…”
Section: Introductionmentioning
confidence: 99%